James Constantine Hanges, Paul, Founder of Churches. A Study in Light of the Evidence for the Role of “Founder-Figures” in the Hellenistic-Roman Period (WUNT I/292; Tübingen: Mohr Siebeck 2012) - Kowalski, Marcin (The Biblical Annals, 2015)
Book review: James Constantine Hanges, Paul, Founder of Churches. A Study in Light of the Evidence for the Role of “Founder-Figures” in the Hellenistic-Roman Period (WUNT I/292; Tübingen: Mohr Siebeck 2012). Pp. 550 + XXIII. € 129.00. ISBN 978-3-16-150716-8.